Ø¯Ø±Ø§Ø³Ø§Øª ÙÙ Ø¹ÙÙÙ Ø§ÙÙØ±Ø¢Ù Ø§ÙÙ Ø¹Ø§ØµØ±: Ù ÙÙÙ Ø§ÙØ³Ø± Ø³ÙØ¯ Ø£ØÙ Ø¯ Ø®Ø§Ù Ù Ù Ø¥Ø¹Ø¬Ø§Ø² Ø§ÙÙØ±Ø¢Ù Ø§ÙÙØ±ÙÙ - Maghribi, Hamdan (State Institute of Islamic Studies (IAIN) Palu, 2016)
This paper deals with the Iâjaz Alquran according to Sir Syed Ahmad Khan. It is concluded that Khan toughly emphasized his interpretation concept on rationalism. Khan also applied it for Quranic studies, such as emphasizing on rational and scientific facts that negate several metaphysical and invisible issues contained in Qurâan. Following his view on the prophetsâ miracle which is irrational and unacceptable for human mind. Again, the concept of Iâjaz Alquran is also one of Khanâs thought on rationality, though he acknowledged the great literary contents of Quran, as well he uncategorized it as a miracle. He then said that Godâs challenge human to afford the similar verses to Qurâan is unclassified among Iâjaz Qurâan, since God did the similar thing to the book of Torah as well. Unlike the opinion of majority Tafseer scholars, among the Salaf and Khalaf, they viewed that Godâs challenge and the Quran high literature are evidence of Iâjaz Quran.